Evidence-based medicine and clinical guidelines: solution or problem? - Bignamini, Angelo A. (Medicina e Morale, 2001)
Evidence-based medicine (EBM) and clinical practice guidelines are widely used to take decisions in the medical field. They surely have the advantage to effectively synthesise in handy statements and numbers the large amount of clinical information constantly produced in today's world. They can also lead to the definite exclusion from medical practice of objectively useless or damaging procedures. However, the risks associated to their incorrect use should not be overlooked. Both EBM and guidelines suffer of the structural limitation of being limited in coverage, since only procedures in principle not necessary can become object of evidence. They are both limited in their applicability to the individual patient, since the statistical inference on which they are based is applicable to populations, not to individuals. Finally, their very generation can be biased. EMB and guidelines can be a useful tool for the education of healthcare workers and can be an effective support for planning the requisition of available medical resources. Neither, however, can restrict the right of each patient to the best available treatment, nor the right and duty of each physician to apply to each patient the therapeutic approach considered most suitable for that patient under those specific conditions. On the other hand, the physician's compliance with the information originated by the EBM and with the recommendations from the clinical practice guidelines, can at most guarantee that no major mistakes have been done, not to have worked on the best patient's interest, and in an ethically appropriate way.